A study of Antenatal risk factors and fetal outcome in IUGR pregnancies - Shafi Zubair Deeba; Shivani Sachdev Gour (International Journal of Medical Research and Review, 2016)
Introduction: Low birth weight (LBW) (neonate weighing <2500 g) is a multifactorial phenomenon.Many maternal and fetal factors are found significantly to be associated with the low birthweight.Material and Methods: It was a retrospective record based study carried out in tertiary care hospitals in Delhi where the authors work between May 2013 and December 2014. The study population consisted of 200 IUGR cases (babies weighing less than 2 kgs).Results: In our study, maximum 80 (40%) of the IUGR cases found in primigravidas, and minimum 24 (12%) cases were found in 4th gravida. In our study 82 (41%) of the IUGR cases found in Normotensives, 59 (29.5%) cases were found in mild hypertensives and minimum 18 (09%) cases were found in severe hypertensive mothers. In our study 90 (45%) of the IUGR cases found in pregnant women had normal haemoglobulin levels, maximum 56 (28%) cases found in pregnant women had mild anemia and minimum 12 (06%) cases found in pregnant women had severe anemia.Conclusion: From the available literature reviewed it was found that the major risk factor for IUGR was lack of knowledge in the mothers regarding prevention of IUGR. Hence there is a need to assess the knowledge of rural primigravidas mothers and conduct a structured teaching programme on prevention of IUGR.